2017
DOI: 10.5115/acb.2017.50.4.255
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles and strategies preferences of Iranian medical students in gross anatomy courses and their correlations with gender

Abstract: The learning approaches can help anatomy teachers design a suitable curriculum in harmony with their students' learning styles. The research objective is to evaluate gross anatomy learning styles and strategies preferences of Iranian medical students at Kashan University of Medical Sciences (KAUMS). This cross-sectional questionnaire-based study was carried out on 237 Iranian medical students. The students answered questions on approaches to learning anatomy and expressed opinions about learning anatomy in med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…These approaches change over time to include the recommend course material, online platforms and more structured self-directed learning; thus, evolving to become multi-modal. The use of online resources, however, is less than what the authors expected and corresponds to the findings of others (Atlasi et al, 2017). Genderbased differences were not explored and is a possible limitation of this study.…”
Section: Emerging Themes N Frequency (%)supporting
confidence: 55%
See 1 more Smart Citation
“…These approaches change over time to include the recommend course material, online platforms and more structured self-directed learning; thus, evolving to become multi-modal. The use of online resources, however, is less than what the authors expected and corresponds to the findings of others (Atlasi et al, 2017). Genderbased differences were not explored and is a possible limitation of this study.…”
Section: Emerging Themes N Frequency (%)supporting
confidence: 55%
“…The inclusion of the latter is extremely important for educators wishing to shift from a more didactic approach to fostering selfdirected learning amongst students (Lachman and Pawlina, 2006). Furthermore, the ability to characterise students' learning approaches has the potential to enhance the overall educational experience by guiding educators to tailor their teaching approaches and initiate possible remedial interventions (Romanelli et al, 2009;Atlasi et al, 2017). The aim here, through the formal inclusion of reflective practice, is to provide insights to pharmacy students' initial approaches to studying anatomy, promote their metacognition as well as their perceived value of anatomy as a subject.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that males and females interact differently in learning situations [ 24 ], and research found that females perform better with collaborative learning [ 25 ]. Atlasi, Moravveji [ 26 ] indicated that female students were more motivated to learn in small groups than male students. Wehrwein, Lujan [ 27 ] reported that only 4.2% of male students preferred learning by reading printed texts and writing compared to other modes of instruction.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of the residency programs report that gross anatomy is either extremely important or very important to mastery of their discipline and rank it as the most important basic science [1]. The ability to conceptualize and visualize the structure in three-dimensional (3D) space, which is developed in the gross anatomy curriculum, is also important in the clinical setting when operating or performing invasive medical tests [2]. Traditional learning methods in gross anatomy are lecture-based learning, problem-based learning, and dissection [34].…”
Section: Introductionmentioning
confidence: 99%